Global, regional, and national trends in DALYs for blindness and vision loss in teenagers and young adults, 1990–2019: an age-period-cohort analysis based on the Global Burden of Disease Study 2019 - Lu, Juan; Jiang, Xiaoyun; Yu, Hao; Tian, Yanghua; Tao, Liming (Frontiers in Medicine, 2025)
PurposeTo analyze temporal trends in disability-adjusted life years (DALYs) associated with blindness and vision loss in teenagers and young adults at global, regional, and national levels between 1990 and 2019, with particular attention to age, period, and birth cohort.MethodsEstimates were derived from the Global Burden of Disease Study 2019. An age-period-cohort (APC) model was adopted to estimate overall annual percentage changes in DALYs (net drift), annual percentage changes in DALYs within age groups (local drift), fitted longitudinal age-specific rates adjusted for period deviations (age effects), and period- and birth cohort-relative risks (period/cohort effects) between 1990 and 2019. This facilitated the identification of disparities and treatment gaps in eye care.ResultsIn 2019, the global number of DALYs associated with blindness and vision loss in teenagers and young adults was 2085.40 thousand (95% UI: 1340.56 to 3074.23). Among the 204 countries and territories, 40 had DALYs of at least 10,000, with the top five countries (India, China, Brazil, Indonesia, and Pakistan) being responsible for 48% of DALYs globally. The APC model estimated a global net drift at −0.43% (95% CI: −0.45% to −0.42%) per year, ranging from −0.92% (95% CI: −0.94% to −0.91%) in low-middle socio-demographic Index (SDI) regions to −0.03% (95% CI: −0.07% to −0.0005%) in high SDI regions. As reflected by local drift, the DALYs had decreasing trends across all age groups, except in high SDI countries. Age effects illustrated similar patterns across different SDI regions, with risk increasing with age. High SDI region showed generally higher period risks over time, whereas others showed more favorable period risks. High SDI regions presented worsening risks of DALYs, while other regions indicated improving trends of DALYs in successive birth cohorts.ConclusionAlthough an overall favorable trend of DALYs related to blindness and vision loss in teenagers and young adults was observed globally over the past three decades, unfavorable period and cohort effects were found in many countries, raising questions about the adequacy of their eye care across all age groups. Improvements in prevention, treatment, and rehabilitation programs related to blindness and vision loss in teenagers and young adults could reduce the risk for successively younger birth cohorts and for all age groups over time.